2019
DOI: 10.18510/ijsrtm.2019.741
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Pigmented Bacteria Isolated From Malaysian Seawater

Abstract: Purpose of study: Bacteria can naturally produce pigments that can be useful for various applications as they possess antimicrobial metabolites among other numerous benefits towards the human health. This study was carried out to identify the species of marine bacterial isolates PMA, PM3C1 and PM5C1 exhibiting yellow, orange and green colors respectively. Methodology: The current study is using Polymerase Chain Reaction (PCR) amplification and sequence analysis of their 16S rRNA gene. The stability of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the present study, the activity of microorganisms likely resulted in a decrease in the color parameters L* and a* and an increase in the color parameter b* during the storage of turkey muscles ( Table 4 ). Several research studies have demonstrated that specific bacteria have the ability to produce pigments through their metabolic activities, resulting in changes to the natural color of meat, such as an enhancement in its yellowness [ 58 , 59 ]. Furthermore, modification in the color of meat, which includes a rise in yellowness, has been linked to bacterial spoilage, myoglobin autoxidation, and protein oxidation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the activity of microorganisms likely resulted in a decrease in the color parameters L* and a* and an increase in the color parameter b* during the storage of turkey muscles ( Table 4 ). Several research studies have demonstrated that specific bacteria have the ability to produce pigments through their metabolic activities, resulting in changes to the natural color of meat, such as an enhancement in its yellowness [ 58 , 59 ]. Furthermore, modification in the color of meat, which includes a rise in yellowness, has been linked to bacterial spoilage, myoglobin autoxidation, and protein oxidation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%